2021
DOI: 10.4103/jpbs.jpbs_659_20
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Assess the Efficacy of 4% Articaine, 0.5% Bupivacaine and 2% Lignocaine Using a Single Buccal Supraperiosteal Injection for Maxillary Tooth Extraction

Abstract: Introduction: The aim of this study was to demonstrate if articaine hydrochloride administered alone as a single buccal infiltration in maxillary tooth extraction can provide adequate palatal anesthesia as compared to buccal and palatal injection using lidocaine and bupivacaine. Materials and Methods: A prospective double-blinded trial was conducted on 150 patients who required maxillary tooth extraction. The patients were divided into three different groups consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The studies evaluated procedural pain during the extraction of upper permanent maxillary teeth except that of Chandrasekaran et al [43], which included the lower anterior teeth. Five studies -Bataineh et al [35], Kumar et al [36], Saravanan et al [38], Chandrasekaran et al [43], and Phyo et al [47] evaluated procedural pain during the extraction using a subjective score, the visual analog scale (VAS), while the sixth Chandrasekaran et al [43] used an objective score, the facial pain scale (FPS). Bataineh et al [35] found that 62% of the patients (31) in the lidocaine group reported mild pain and 60% (30) patients in the articaine group while 34% of patients (17) in each group reported moderate pain and 4% (two) of the patients in the lidocaine group and 6% (three) of those in the articaine group reported severe pain.…”
Section: Single Buccal Articaine Compared With Single Lidocainementioning
confidence: 99%
See 3 more Smart Citations
“…The studies evaluated procedural pain during the extraction of upper permanent maxillary teeth except that of Chandrasekaran et al [43], which included the lower anterior teeth. Five studies -Bataineh et al [35], Kumar et al [36], Saravanan et al [38], Chandrasekaran et al [43], and Phyo et al [47] evaluated procedural pain during the extraction using a subjective score, the visual analog scale (VAS), while the sixth Chandrasekaran et al [43] used an objective score, the facial pain scale (FPS). Bataineh et al [35] found that 62% of the patients (31) in the lidocaine group reported mild pain and 60% (30) patients in the articaine group while 34% of patients (17) in each group reported moderate pain and 4% (two) of the patients in the lidocaine group and 6% (three) of those in the articaine group reported severe pain.…”
Section: Single Buccal Articaine Compared With Single Lidocainementioning
confidence: 99%
“…The risk of bias (Figure 2 ) was evaluated for each study following the Cochrane guidelines [ 20 ]. Most of the studies involved randomization [ 23 , 29 , 31 , 35 - 38 , 46 - 48 , 51 , 53 ], with four exceptions [ 21 , 28 , 43 , 5 ]. Most also involved allocation concealment, again with four exceptions [ 28 , 45 , 46 , 51 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[29] Bupivacaine is an amide anesthetic and a so-called “long-acting” local anesthetic with a long duration of action and residual analgesia. [30] The long-acting anesthetic and analgesic effects of bupivacaine make the operation comfortable, but prolonged anesthesia in soft tissues is uncomfortable for patients. [31] It has been reported that articaine has better clinical effects than bupivacaine, with shorter latency, less bleeding, shorter soft tissue anesthesia time, better anesthesia efficacy, and lower anesthetic dose than bupivacaine.…”
Section: Introductionmentioning
confidence: 99%